DYNAMIC EVOLUTION OF A FAULT SYSTEM THROUGH INTERACTIONS BETWEEN FAULT SEGMENTS - Ando R.; Yamashita T.; Tada T. (My University, 2004)
We simulate the dynamic evolution process of fault system geometry considering interactions between fault segments. We calculate rupture propagation using an elastodynamic boundary integral equation method (BIEM) in which the trajectory of a fault tip is dynamically self-chosen. We consider a system of two noncoplanar fault segments: a preexisting main fault segment (fault 1) and a subsidiary one (fault 2) and, allowing the tip of fault 2 to deviate from its original plane, trace its trajectory in the step over region between the two fault segments. Our simulation results show that the final geometry of fault 2 depends on the initial configuration of the two fault segments. If the initial overlap of the two fault segments is smaller than the half length of fault 1, fault 2 coalesces with fault 1 when the step over is narrower than about 1/4–1/2 the length of the latter but is repelled from fault 1 when the step over width is larger than this threshold value. We also show that the inclination angle of fault 2 is sensitive to the rupture velocity; the inclination is larger for faster rupture propagation. Our simulation results imply that as ruptures occur repeatedly, a fault system evolves from an array of relatively small fault segments into a sequence of larger ones. Our results seem consistent with the field observations of natural fault system geometries, which are often characterized by a set of noncoplanar segments interconnected with relatively small jogs at oblique angles.
Keywords: rupture dynamics; fault interactions; fault geometry